Zfp462 deficiency causes anxiety‐like behaviors with excessive self‐grooming in mice. (7th October 2016) - Wang, B.; Zheng, Y.; Shi, H.; Du, X.; Zhang, Y.; Wei, B.; Luo, M.; Wang, H.; Wu, X.; Hua, X.; Sun, M.; Xu, X.
Abstract : Zfp462 is a newly identified vertebrate‐specific zinc finger protein that contains nearly 2500 amino acids and 23 putative C2H2‐type zinc finger domains. So far, the functions of Zfp462 remain unclear. In our study, we showed that Zfp462 is expressed predominantly in the developing brain, especially in the cerebral cortex and hippocampus regions from embryonic day 7.5 to early postnatal stage. By using a piggyBac transposon‐generated Zfp462 knockout (KO) mouse model, we found that Zfp462 KO mice exhibited prenatal lethality with normal neural tube patterning, whereas heterozygous (Het) Zfp462 KO (Zfp462 +/− ) mice showed developmental delay with low body weight and brain weight. Behavioral studies showed that Zfp462 +/− mice presented anxiety‐like behaviors with excessive self‐grooming and hair loss, which were similar to the pathological grooming behaviors in Hoxb8 KO mice. Further analysis of grooming microstructure showed the impairment of grooming patterning in Zfp462 +/− mice. In addition, the mRNA levels of Pbx1 (pre‐B‐cell leukemia homeobox 1, an interacting protein of Zfp462) and Hoxb8 decreased in the brains of Zfp462 +/− mice, which may be the cause of anxiety‐like behaviors. Finally, imipramine, a widely used and effective anti‐anxiety medicine, rescued anxiety‐like behaviors and excessive self‐grooming in Zfp462 +/− mice. In conclusion, Zfp462 deficiency causes anxiety‐like behaviors with excessive self‐grooming in mice. This provides a novel genetic mouse model for anxiety disorders and a useful tool to determine potential therapeutic targets for anxiety disorders and screen anti‐anxiety drugs. Abstract : Zfp462 deficiency causes anxiety‐like behaviors.